Environmental science : action for a sustainable future - Chiras, Daniel D (Benjamin/Cummings, 1990)
Presenting sustainability as an overarching theme essential to rethinking current policies and practices, this book highlights positive efforts towards implementing sustainability. It presents the key principles of sustainability in the first chapter and develops them throughout the text. The book emphasizes global environmental concerns and presents students with opposing viewpoints on relevant environmental issues and offers them opportunities to apply critical thinking. In this revised edition, four regional versions have been developed to address environmental issues in four different areas of the USA. There are also three new chapters: principles of science and ecology - addressing the sustainable imperative; global environmental challenges - ozone depletion, acid deposition and global warming; and sustainable economic development - challenges facing the developing nations. There are also new critical-thinking exercises which open each chapter with a challenge and end each chapter with a solution.
Keywords: Environment; životní prostředí